Escherichia coli contamination of rural well water in Alberta, Canada is associated with soil properties, density of livestock and precipitation. Issue 3 (3rd July 2019) - Invik, Jesse; Barkema, Herman W.; Massolo, Alessandro; Neumann, Norman F.; Cey, Edwin; Checkley, Sylvia
Abstract: Waterborne outbreaks of infectious disease continue to be a public health risk, particularly those in areas where testing of private and public small system groundwater systems is left to the owners/overseers of these wells who may not recognize the importance of testing and treatment. Recognizing factors associated with contamination of wells is important for public safety and can encourage well owners/overseers to test regularly and properly maintain drinking water supplies. Tests results for presence/absence of total coliforms and Escherichia coli for private and public untreated well water for the years 2010-2012 (n = 56, 609) were provided by the Alberta Provincial Laboratory for Public Health. Tests were geolocated with the Alberta Township Survey System and aggregated to the quarter section. Agricultural independent variables were provided by the Canadian Agricultural Census and monthly cumulative precipitation was calculated using Alberta Agriculture and Forestry's website of weather station data. Overall frequency of E. coli -positive wells in the study was 1.4%. A marginal multivariable logistic regression model was fit using generalized estimating equations to account for repeat testing of some quarter sections. Three significant factors associated with increased E. coli -positive untreated drinking water wells were identified: soil properties (KSat and sand content), animal density and monthly cumulative precipitation.